2021
DOI: 10.1088/1755-1315/905/1/012138
|View full text |Cite
|
Sign up to set email alerts
|

Potential effect of some essential oils on rumen methane reduction and digestibility by In Vitro incubation technique

Abstract: Since excessive use of in-feed antibiotics and chemical feed supplements can potentially affect health risks and environmental problems, organic feed supplement became alternative save material. Organic material such as essential oils (EO) is potential for feed additive in the livestock industry because of their main activity as rumen manipulator. Their potential as rumen manipulators has not enough for type and doses of essential oils experiment. Therefore, the objective of this study was to evaluate 6 essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…The use of 0.5% OEO reduced rumen microbial activity, which affected the fermentability, degradability, and CH 4 emissions ( 47 ). This is consistent with findings of in vitro studies showing that 200 and 300 ppm of orange peel oil inhibits CH 4 generation by more than 50% due to the low digestibility of DM and NDF, which was possibly associated with a microbial imbalance in the rumen ( 48 ). The discrepancies among studies might be caused by different types of EOs that were used in the respective studies, dosages tested, and differences in diet and host interactions ( 49 ).…”
Section: Discussionsupporting
confidence: 91%
“…The use of 0.5% OEO reduced rumen microbial activity, which affected the fermentability, degradability, and CH 4 emissions ( 47 ). This is consistent with findings of in vitro studies showing that 200 and 300 ppm of orange peel oil inhibits CH 4 generation by more than 50% due to the low digestibility of DM and NDF, which was possibly associated with a microbial imbalance in the rumen ( 48 ). The discrepancies among studies might be caused by different types of EOs that were used in the respective studies, dosages tested, and differences in diet and host interactions ( 49 ).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, evaluating oregano EO at doses of 150 ppm and 0.5 mg/L showed a real reduction in IVDMD and gas production parameters on various test substrates (Kilic et al, 2011;Righi et al, 2017). Conversely, adding EO doses of clove, mint, and cinnamon of up to 300 ppm showed increased rumen organic matter digestibility in vitro (Rofiq et al, 2021). In addition, EO have a stronger toxic effect than condensed tannin on rumen methanogens (Cieslak et al, 2013), 0.50% orange EO (78.84% D-Limonene) contributed to a 12% reduction in ruminant methane production (Jiménez-Ocampo et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…Although there was no difference in the concentrations of iso‐acid (such as iso‐butyric, iso‐valeric and iso‐caproic acids), which are a by‐product of ruminal protein catabolism, for the three phenological stages, the ruminal ammonia‐nitrogen concentration in the seed bulking stage was lower than in other stages can be related to the decreased ruminal protein catabolism due to the increase in the fiber‐nitrogen complex ratio or TCT in this stage (Kara et al, 2022a ; Kara, 2019 ). A previous study reported that increasing additions of mint essential oil, which included 39.98% pulegone and 38.99% α‐pinene, to the total mix ration linearly reduced in vitro ruminal methane production (Rofiq et al., 2021 ). Besides all these positive results, pennyroyal has a traditional folk medicine use in inducing abortions.…”
Section: Discussionmentioning
confidence: 99%